2012
DOI: 10.4293/108680812x13462882737177
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Robotic, Laparoscopic and Open Partial Nephrectomy

Abstract: Renal function preservation and complications were similar for robotic, laparoscopic, and open partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 23 publications
7
60
1
2
Order By: Relevance
“…3 studies [10], [12], [28] reported the intraoperative renal artery unclamping rate and the pooled data revealed a significantly higher rate in the OPN group than the RPN group (OR: 0.60; 95%CI, 0.38–0.95; p = 0.03) (Fig.2g). …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…3 studies [10], [12], [28] reported the intraoperative renal artery unclamping rate and the pooled data revealed a significantly higher rate in the OPN group than the RPN group (OR: 0.60; 95%CI, 0.38–0.95; p = 0.03) (Fig.2g). …”
Section: Resultsmentioning
confidence: 96%
“…The following studies are cited: Alemozaffar et al 2013 [26], Laydner et al 2013 [27], Lee et al 2011 [10], Lucas et al 2012 [28], Masson-Lecomte et al 2013 [11], Minervini et al 2013 [12], Simhan et al 2012 [13], Yu et al 2012 [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38,39] In a study by Marszalek et al [40] , the authors reported relatively decreased warm ischemia times, but comparable amounts of blood loss in laparoscopic technique when compared with OPN. Lucas et al [41] performed a study on 96 patients with SRMs with similar size (2.3 cm), and a nephrometry score of 6, and reported comparable levels of preservability of renal functions, complication rates, and surgical margin positivity for all three methods. In the OPN group, mean operative time (147 min), and duration of warm ischemia (12 min) were reportedly decreased, while authors noted relatively increased blood loss (250 mL), and median hospital stay (3 days).…”
Section: Discussionmentioning
confidence: 99%
“…There were no positive surgical margins. The reported rates of positive surgical margins with LPN were 0% to 4% [18192021222324]; the rate of the historical control was 1.7%. These values indicate the effectiveness of RAPN for cancer control.…”
Section: Clinical Trial Of Rapn In Japanmentioning
confidence: 99%